MENCARI JATI DIRI : PERAN PEER GROUP DALAM MEMBENTUK IDENTITAS REMAJA - Juwita Salwa Leswidyanti; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (Yayasan Literasi Sains Indonesia, 2025)
This study discusses the process of identity search in adolescents and peer group factors that influence adolescent identity. Adolescence is a period of significant change in an individual's life, where they try to find self-identity and determine the direction of their life goals. The formation of adolescent identity is influenced by various factors, including interactions with peers (peer groups). Peers can play an important role in shaping the character and identity of adolescents through social interactions and emotional support. The purpose of this study is to identify the role of peer groups as a factor shaping identity in adolescents. The author used the study method review to describe the role of peer groups as a factor shaping identity in adolescents. The results showed that peers have a significant role in the formation of adolescent identity, with positive and negative impacts that can affect various aspects of adolescent life, including style of dress, behaviour, academic achievement, and psychological well-being. Thus, it can be concluded that peers have a very significant role in the formation of adolescent identity, with both positive and negative impacts that can affect various aspects of adolescent life. Therefore, it is important to understand the role of peers in adolescent identity formation and consider its implications in the context of adolescent education and development.